Overview of the Rapid Antidepressant Effects Observed in the Zuranolone Clinical Development Program [A164]. (May 2022) - Clayton, Anita H.; Deligiannidis, Kristina M.; Kotecha, Mona; Doherty, James
Abstract : INTRODUCTION: Zuranolone is an investigational oral neuroactive steroid in clinical development for once-daily, 2-week treatment of postpartum depression (PPD) and major depressive disorder (MDD) in the NEST and LANDSCAPE clinical development programs, respectively. Here we review the rapid antidepressant effects and the safety of zuranolone in four completed placebo-controlled studies in these programs. METHODS: ROBIN (NCT02978326; Phase 3; zuranolone 30 mg [ZRN30]; baseline 17-item Hamilton Rating Scale for Depression total score [HAMD-17] ≥26; N=153) in PPD; MDD-201B (NCT03000530; Phase 2; ZRN30; baseline HAMD-17 ≥22; N=89 [62% women]), MOUNTAIN (NCT03672175; Phase 3; zuranolone 20 mg or ZRN30; baseline HAMD-17 ≥22; N=581 [70% women]), and WATERFALL (NCT04442490; Phase 3; zuranolone 50 mg; baseline HAMD-17 ≥24; N=543 [66% women]) in MDD. All studies were institutional review board‒approved. RESULTS: Treatment with zuranolone led to rapid and nominally significant improvements in depressive symptoms versus placebo (as assessed by least squares mean treatment difference [SE] in change from baseline in HAMD-17) as early as Day 3 in ROBIN (−2.7 [1.19], P =.025), MOUNTAIN (ZRN30, −1.5 [0.64], P =.0160), and WATERFALL (−3.0 [0.52], P <.0001) and Day 2 in MDD-201B (−2.3 [0.99], P =.0223). Treatment-emergent adverse events (incidence ≥5% in zuranolone arms) included headache, somnolence, dizziness, nausea, sedation, diarrhea, upper respiratory tract infection, fatigue, and dry mouth (≥94% mild to moderate in severity). No loss of consciousness or excessive sedation were observed in any of the studies. CONCLUSION: These data from the NEST and LANDSCAPE clinical development programs demonstrate that treatment with zuranolone can lead to rapid improvement in depressive symptoms with a generally well-tolerated safety profile.